2014
DOI: 10.1177/0362153714545312
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge and Potential of the Digital Age

Abstract: This article offers reflections on young people’s use of cyberspace and the role social media and relating in cyberspace plays in their development. The author outlines a model of working based on ego state diagnosis and Hargaden and Sill’s (2002) model of the self, which she uses to identify how to respond clinically and support these adolescents in their engagement with e-therapy. She touches on some of the complexities of working online in relation to anonymity, confidentiality, and child protection to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Young people discussed the Internet more generally and social media such as Instagram and Facebook and how they used them to connect with others and offer each other advice on online safety. Supporting previous findings related to the affordances of the Internet benefiting young people seeking support online [ 5 , 13 - 15 , 31 ]. This may also potentially link to previous literature [ 27 ], suggesting that young people feel comfortable discussing issues outside of the topic areas not necessarily related to mental health issues.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Young people discussed the Internet more generally and social media such as Instagram and Facebook and how they used them to connect with others and offer each other advice on online safety. Supporting previous findings related to the affordances of the Internet benefiting young people seeking support online [ 5 , 13 - 15 , 31 ]. This may also potentially link to previous literature [ 27 ], suggesting that young people feel comfortable discussing issues outside of the topic areas not necessarily related to mental health issues.…”
Section: Discussionsupporting
confidence: 88%
“…The Internet affords a number of features the offline world does not. Research has found many of these features are important for young people seeking health information and offering support [ 5 ]. One feature of the Internet is that social cues are limited [ 6 ], which allow users to engage with those with whom they would otherwise not do so in the offline world [ 7 ], and it produces a hyperpersonal interaction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a UK study posits that young people are continuously exploring and recognising the affordances of social media (Berriman & Thomson, 2015). The internet is increasingly accessed for health information and services, since it affords convenience and anonymity, factors that are shown to be especially appealing for young people within the UK and USA (Gray et al, 2005;Evans, 2014;Fox & Duggan, 2013). Thus, online mental health services therefore have the potential to reach young people and offer them an avenue for both professional and peer support (Horgan, McCarthy, & Sweeney, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Julia Davidson and Elena Martellozzo (2013) observe that everything young people-and by extension older university students-do online is a permanent record of their actions, "a digital footprint that may impact negatively upon career opportunities and relationships" (p. 1472). Evans (2014) concurs, stating that "cyberspace is public" and everything that is uploaded stays there, even though young people may experience it as anonymous (p. 161). Therefore, questions of cyberbullying need to be understood as part of bigger questions about how disrespectful behaviours and communications in online spaces can be permanently damaging to a student beyond their time at university.…”
Section: Digital Footprint Digital Wellness and Reputationmentioning
confidence: 99%